Anatomical Differences between Children and Adults (International Journal of Scientific Research and Management (IJSRM), 2020)
In this review, anatomical differences between child and adult were mentioned. These differences are especially apparent in infancy and preschool term. When the child reaches the school age term, the differences begin to decrease gradually. When the child reaches the age of 18, the child has the same characteristics as the adult. The main differences include skin, subcutaneous tissue, total amount of water in the body, muscles preferred in pharmaceutical applications, external ear structure, Eustachian tube, anatomy of the eye, bone skeletal structure, spinal cord and brain, respiratory tract, digestive organs, cardiovascular system and urinary system. The differences especially between child and adult brain structure are striking. The brain tissue in the child is more sensitive, calvarium is thinner, subarachnoid space is narrower. Morover; the differences in gynecological examination and lumber puncture practices were also reviewed. In adults, gluteal muscles are used in intramuscular applications, while in infants, rectus femoris and vastus lateralis muscles are commonly used. These anatomical differences are important for the diagnosis and treatment of the doctors. Nurses should take these differences into account in pediatric drug applications in the clinic and in the care of children. Clinicians should know that children are not small adults.